Preparation of immobilized arylsulfatase on magnetic Fe3O4 nanoparticles and its application for agar quality improvement. Issue 9 (7th July 2021) - Zhang, Chenghao; Jiang, Zedong; Li, Hebin; Ni, Hui; Zheng, Mingjing; Li, Qingbiao; Zhu, Yanbing
Abstract: The presence of sulfate groups in agar compromises the agar quality by affecting the crosslinking during gelling process. Some arylsulfatases can catalyze the hydrolysis of sulfate bonds in agar to improve the agar quality. Immobilized arylsulfatases prove beneficial advantages for their industrial applications. Here, a previously characterized mutant arylsulfatase K253H/H260L was immobilized on the synthesized magnetic Fe3 O4 nanoparticles after functionalization by tannic acid (MNPs@TA). The surface properties and molecular structures of the immobilized arylsulfatase (MNPs@TA@ARS) were examined by scanning electron microscopy and Fourier transform infrared spectroscopy. Enzymatic characterization showed that MNPs@TA@ARS exhibited shifted optimal temperature and pH with deviated apparent Km and Vmax compared to its free counterpart. The immobilized arylsulfatase demonstrated improved thermal and pH stability and enhanced storage stability with modest reusability. In addition, MNPs@TA@ARS displayed enhanced tolerance to various inhibitors and detergents. The utilization of the immobilized arylsulfatase for agar desulfation brought the treated agar with improved quality. Abstract : An arylsulfatase of marine bacterial origin was immobilized on the magnetic nanobeads. The immobilized arylsulfatase had enhanced thermal and pH stability. After treatment of agar by the immobilized enzyme, agar had equivalent quality to agarose.